2016
DOI: 10.22146/jieb.10322
|View full text |Cite
|
Sign up to set email alerts
|

Extended Theory of Planned Behavior as Model of Anabolic Androgenic Steroid Use by Indonesian Bodybuilders

Abstract: This correlational study explored the psychological antecedents of Indonesian bodybuilders' intentions to use anabolic-androgenic steroids (AAS), based on the Theory of Planned Behavior (TPB). The purpose of this research was to identify factors that influence an Titah and Barki (2009), as suggested by Chang (1998) and Aarts et al. (1998), who stated that a person whose positive subjective norms move them toward overt behavior, it will lead to a positive attitude toward the behavior. Future research direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
2
2
0
2
Order By: Relevance
“…2 ), as behavioral willingness and attitude have the greatest effect on predicting behavioral intention. In the study by Patiro et al, there was a direct relationship between attitude and behavioral intention of AAS use, which is consistent with the results of the present study [ 33 ]. As well, in the study by Abedini et al, attitude, subjective norms, and behavioral willingness were reported as the predictors of intention to use hookah among students [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…2 ), as behavioral willingness and attitude have the greatest effect on predicting behavioral intention. In the study by Patiro et al, there was a direct relationship between attitude and behavioral intention of AAS use, which is consistent with the results of the present study [ 33 ]. As well, in the study by Abedini et al, attitude, subjective norms, and behavioral willingness were reported as the predictors of intention to use hookah among students [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…2), as behavioral willingness and attitude have the greatest effect on predicting behavioral intention. In the study by Patiro et al, there was a direct relationship between attitude and behavioral intention of AAS use, which is consistent with the results of the present study [33]. As well, in the study by Abedini et al, attitude, subjective norms, and behavioral willingness were reported as the predictors of intention to use hookah among students [17].…”
Section: Discussionsupporting
confidence: 92%
“…Deliberative attitude assessment adapted to specific research context often utilize semantic differential measures (e.g., Barkoukis et al, 2014;Chantal & Bernache-Assollant, 2015;Girelli et al, 2020;Horcajo & Luttrell, 2016;Horcajo et al, 2019;Horcajo et al, 2020;Lazuras et al, 2010;Patiro et al, 2016;Psouni et al, 2015). Items for this type of attitude measure typically ask respondents to place the concept of doping (in general) or a specific doping behavior between the extreme ends of semantic differential pairs.…”
Section: Measuring Doping Attitudes With Scaled Semantic Differential Itemsmentioning
confidence: 99%